2020
DOI: 10.1002/iub.2311
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin protects against testicular injury induced by lead acetate by activating the Nrf2/HO‐1 pathway

Abstract: Lead (Pb) is a toxic heavy metal that is harmful to humans, especially male reproductive organs. Luteolin (LUT) is a naturally occurring flavonoid with numerous biological activities. Our aim was to investigate the possible reproprotective effect of LUT against testicular deficits induced by Pb intoxication. In the present study, 28 rats were distributed into 4 groups: control, LUT (50 mg/kg), lead acetate (PbAc, 20 mg/kg), and LUT + PbAc groups, in which rats were pre‐treated with LUT 3 hr before PbAc injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
3
28
0
1
Order By: Relevance
“…Spermatozoa have a high content of polyunsaturated fatty acids. Therefore, it is thought to be extremely sensitive to reactive oxygen species (AL‐Megrin et al., 2020; El‐Khadragy et al, 2020). Oxidative stress plays an important role in the formation of Pb toxicity by damaging sperm membranes, proteins, and DNA (Ezejiofor & Orisakwe, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatozoa have a high content of polyunsaturated fatty acids. Therefore, it is thought to be extremely sensitive to reactive oxygen species (AL‐Megrin et al., 2020; El‐Khadragy et al, 2020). Oxidative stress plays an important role in the formation of Pb toxicity by damaging sperm membranes, proteins, and DNA (Ezejiofor & Orisakwe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, it has been reported that PbAc suppresses the antioxidant defense system and causes lipid peroxidation. (Abdrabou et al., 2019; AL‐Megrin et al, 2020; Rao et al., 2016). In the present study, it was detected that PbAc weakened antioxidant defense and resulted in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed nuclear translocation of Nrf2, along with the dose-dependent decrease in GST and GSH, suggesting that the multidrug resistance protein 1 (Mrp1), which was also upregulated upon Pb exposure, might play important roles in lead detoxification by Nrf2 [ 89 ]. The authors speculated that overactivation of nuclear factor kappa B (NF-κB) by free radical overproduction increased the level of Keap1, leading to Nrf2 impairment and a decrease in its antioxidant effects [ 90 ].…”
Section: Determining Toxic Elements Role In Nrf2 Signalingmentioning
confidence: 99%
“…Luteolin exhibits antioxidative property in lipopolysaccharide-stimulated murine macrophages through transforming growth factor betaactivated kinase 1 TAK1 inhibition and Nrf2 activation [66]. Luteolin also enhances the antioxidative process in intracerebral hemorrhage and testicular injury by activating the p62-Keap1-Nrf2 [67] or Nrf2/HO-1 pathway [68]. Moreover, p21 upregulation and mTOR signaling inhibition are involved in the antioxidant effect of luteolin [69].…”
Section: Tcm-based Bioactive Compounds Andmentioning
confidence: 99%